The Development of Digital Teaching Materials: An Effort to Create Mathematics Learning Effectively at Universitas Muhammadiyah Sumatera Utara in the New Normal Era - Nasution, Ismail Saleh; Batubara, Ismail Hanif (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The process of learning conducted by lecturers in higher education currently obliges the student learning activities which are derived from the student centered learning (SCL) approach. This active learning must also be integrated with website-based IT information technology. Internet-based learning is a learning model that uses internet and web-based technology in accessing learning materials and allows learning interactions between fellow students or with lecturers anywhere and anytime.Â  On this origin, this research intends to develop digital teaching materials that can be accessed by students at any time because they are integrated with Android. This research uses development research (r&d) methods. In this research, the phases taken are: 1) designing digital teaching materials, validating design experts and material experts. The outcomes proved that the design for developing internet-based teaching materials was carried out in three phases, that is the needs analysis phase (PDP UMSU 2020), the design phase, and the development and implementation phase.Â  In the design phase, expert validation is carried out. The outcomes of the validation of the material content experts are in good qualification (88%), the outcomes of the validation of the learning design experts are in good qualifications (80%). Thus, it can be concluded that internet-based teaching materials are effective for improving student learning outcomes at the Fakultas Keguruan dan Ilmu Pendidikan (FKIP) UMSU during the new normal period after the Covid 19 pandemic.